Analisis implementasi sistem akuntabilitas kinerja instansi pemerintah pada Badan Keuangan Daerah Kabupaten Manggarai Timur - Priska Nirmala Stefan; Jantje Tinangon; Dhullo Afandi (Riset Akuntansi dan Portofolio Investasi, 2023)
Performance Accountability System for Government Agencies is a system whose application is useful for measuring performance and assisting in improving performance. Accountability has so far been considered to focus only on the preparation of financial statements, and there are even entities that have an understanding that accountability itself is limited to budgetary accountability, which causes total accountability only for reporting on the use of funds without an evaluation of the benefits of activities. Presidential Regulation Number 29 of 2014 forms the foundation for guidelines regarding the Implementation of the Performance Accountability System for Government Agencies. The preparation of SAKIP according to this regulation must encompass various significant components, including Strategic Plans, Performance Agreements, Performance Measurement, Performance Data Management, Performance Reporting, as well as Reviews and Evaluation. The Regional Financial Board of East Manggarai Regency have implemented the Performance Accountability System of Government Agencies successfully. This study aims to determine the compatibility of the application with current regulations, as well as the level of success and failure. The research uses descriptive qualitative methods and collects data through interviews and documentation. The results showed that the implementation of the Performance Accountability System for Government Agencies at the Regional Financial Board of East Manggarai Regency was good and can be said to be in accordance with applicable laws and regulations. The joint commitment of employees, as well as each part in carrying out their responsibilities, was the success factor of the implementation of this SAKIP.